043 Is the prevalence of autism spectrum disorder decreased in black and ethnic children and adolescents?. (December 2018) - John, J; Sala, R
Abstract : Background: A general perception is that ASD occurs equitably across demographic groups and there is no biological basis for a difference in prevalence between different ethnicities. A delayed pattern of diagnosis may be present in BME populations, but little information is available about variations in prevalence by ethnicity. Factors that seem to influence ethnic variability across studies include the case ascertainment approach, immigration status and access to care. A literature review examined the prevalence of childhood Autism Spectrum Disorder (ASD) in Black and Minority Ethnic (BME) populations. Our hypothesis was that the prevalence of childhood ASD in BME populations would be decreased compared to their White counterparts. Methods: A computer-assisted search identified articles about the prevalence of childhood ASD in ethnic minorities. 7 search terms for ASD were linked with 'OR'. Ethnicity search terms linked with 'OR' were: Ethnic group*, Minority group*, Black and ethnic minorit*, BME. The above two were linked with 'prevalence' by 'AND'. Results: We found 8 studies. ASD was assessed using DSM IV criteria. Methods of ascertaining ethnic groupings varied: in the US authors compared White vs Black, Hispanic and Asian ethnicity. In Israel, authors compared Jewish vs Arab and in the Netherlands, white Dutch vs minority European (English/French) vs non-European (Turkish/Moroccan). All studies showed a decreased prevalence of childhood ASD in ethnic minority populations. Possible reasons for this disparity included a cultural understanding of neurodevelopmental disorders, primary language spoken at home, maternal education, the severity of ASD and professional bias. Conclusions: The prevalence of childhood ASD in BME populations is lower compared to their White counterparts. It is influenced by cultural values, with the diagnosis not being recognised in minority groups. This influences the wellbeing of children with ASD from already disadvantaged BME populations. Therefore, there is a need to provide education and better care